Connecting the right to health and anti-extractivism globally - Erika Arteaga-Cruz; Baijayanta Mukhopadhyay; Sarah Shannon; Amulya Nidhi; Todd Jailer (Centro Brasileiro de Estudos de Saúde, 2020)
ABSTRACT Natural resources are essential to health and are global commons. Recognizing the devastating damage posed by extraction to health and the environment, as well as the erosion of the sovereignty of our governments that have increasingly conceded people's health in the interest of profit and development, is important in framing our resistance. Our communities experience growing displacement, the loss of social services, of land, water and livelihood, heightened militarization, violence and repression, and increased incidence of communicable diseases and health problems resulting from exposure to toxics. All of these are linked to an extractivist project driven by global financial capital promoting an unsustainable and inequitable development model that threatens people's health and the health of the planet. Is it compatible with the right to health to finance national health systems with revenues of activities that intrinsically destroy life? The essay portrays the inconsistency of development policies that fund health/right to health with extractivism and depicts examples of resistance to extractive industries tied to the People's Health Movement (Canada,Turkey, India and Ecuador) in different types of governments. The need to strengthen the link between the right to health struggles and anti-extractive resistance is highlighted.